Monitoring young lifestyles (MyLife) - a prospective longitudinal quantitative and qualitative study of youth development and substance use in Norway - Janne Scheffels; Geir Scott Brunborg; Rikke Tokle; Kristin Buvik; Elisabeth Kvaavik; Jasmina Burdzovic Andreas (BMJ Open)
Purpose The Monitoring Young Lifestyles (MyLife) project was initiated as an integrated quantitative and qualitative prospective investigation of correlates, causes, and consequences of adolescent substance use and other addictive behaviours in Norway.Participants The MyLife cohort was recruited from middle schools in Norway, which were selected from low, medium and high standard of living areas in both rural and urban regions of the country. A total of 3512 eighth, ninth and tenth graders (55% girls) from 33 schools were enrolled in the quantitative project arm (QT), while a total of 120 eighth graders (52% girls) from six schools were enrolled in the qualitative project arm (QL).Findings to date QT baseline was conducted in the fall of 2017, when 2975 adolescents completed an online questionnaire at school during a regular class time. A total of 2857 adolescents participated in the first QT follow-up 1 year later. QL baseline was conducted across the fall semesters of 2014 (one class) and 2015 (five classes), when a total of 118 eighth graders completed face-to-face interviews. QL follow-ups were conducted in the spring of 2015 and fall of 2017 (n=98) for group interviews, and in the spring of 2017 and 2018 (n=95) for individual interviews. In terms of additional data sources, a total of 3035 parents consented to own participation, of which 1899 completed a brief online questionnaire at QT baseline in late 2017. School principals completed brief surveys at the same time.Future plans Both QT and QL arms have planned follow-ups through 2021. Consents were obtained for individual-level linkages of adolescent and parental quantitative surveys to each other, as well as to the information available in multiple national registries and databases. These supplemental data sources will provide key information on additional putative exposures as well as on the long-term health, educational, and social outcomes of the MyLife participants.